A mechanoelectrical coupling model of neurons under stretching. (May 2019) - Tian, Jin; Huang, Guoyou; Lin, Min; Qiu, Jinbin; Sha, Baoyong; Lu, Tian Jian; Xu, Feng
Abstract: Neurons are situated in a microenvironment composed of various mechanical cues, where stretching is thought to have a major impact on neurons, resulting in microstructural changes in neural tissue and further leading to abnormal electrophysiological function. In spite of significant experimental efforts, the underlying mechanism remains elusive, more works are needed to provide a detailed description of the process that leads to the observed phenomena. Here, we developed a mechanoelectrical coupling model of central neurons under stretching and specially considered the plastic deformation of neurons. With the model, we showed that the increasing axial strain induces a decreased membrane action potential and a more frequent neuronal firing, which agree well with experimental observations reported in the literature. The simulation results also showed a faster electrophysiological signal conduction. Our model provides a reference for the prediction and regulation of neuronal function under simplified conditions of mechanical loadings.